2004
DOI: 10.1046/j.0894-0959.2004.16086.x
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behavior Disorders in Uremia: A Question of Balance in Appetite Regulation

Abstract: Eating and appetite disorders are frequent complications of the uremic syndrome which contribute to malnutrition in dialysis patients. The data suggest that uremic anorexia may occur with or without abdominal and visceral fat accumulation despite a lower food intake. This form of obesity (i.e., with low food intake and malnutrition) is more common in dialysis patients than obesity with high food intake. This article reviews the current knowledge regarding mechanisms responsible for appetite regulation in norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 74 publications
(105 reference statements)
1
37
0
1
Order By: Relevance
“…[46][47][48][49][50] If effective interventions are targeted to MHD patients most in need, they are likely to narrow the female-male gaps in gastrointestinal symptoms and nutritional status. [46][47][48][49][50] Nausea, vomiting, and reduced appetite in patients with chronic renal failure may be related to the intake of specific types of foods. 48,49 Moreover, the susceptibility to nausea and vomiting seems to be more strongly related to aversion to certain types of foods in women than in men.…”
Section: Discussionmentioning
confidence: 98%
“…[46][47][48][49][50] If effective interventions are targeted to MHD patients most in need, they are likely to narrow the female-male gaps in gastrointestinal symptoms and nutritional status. [46][47][48][49][50] Nausea, vomiting, and reduced appetite in patients with chronic renal failure may be related to the intake of specific types of foods. 48,49 Moreover, the susceptibility to nausea and vomiting seems to be more strongly related to aversion to certain types of foods in women than in men.…”
Section: Discussionmentioning
confidence: 98%
“…129 This clinical situation is characterized by low concentrations of large neutral and branched chain amino acids in the cerebrospinal fluid that can promote a high level of tryptophan transport across the blood-brain barrier, enhance the synthesis of 5-hydroxytryptamine, and results in a reduction in appetite. 130 Furthermore, elevated concentrations of proinflammatory cytokines, such as leptin, free tryptophan, and 5-hydroxytryptamine in the cerebrospinal fluid, combined with a lack of neural nitric oxide and disorders in receptors such as melanocortin receptor-4, can further contribute to anorexia in the uraemic state. 129 Other consequences of uraemia on CNS function Studies using rat models of uraemia have demonstrated that increases in cytosolic calcium levels within synaptosomes are mediated by parathyroid hormone.…”
Section: Cognitive Impairment In Uraemiamentioning
confidence: 99%
“…For instance, H. pylori has been reported to confer protective effects against esophageal cancer (Islami & Kamangar 2008), but on the other hand, together with hepatitis B and C viruses, and human papillomaviruses, the bacterium is responsible for about a third of all cancers attributable to infections, mainly including gastric, liver, and cervix uteri cancers (de Martel et al 2012, Sakitani et al 2012. In addition, silent infection with H. pylori is a source of pro-inflammatory cytokines and IGF1 in hyperinsulinemia conditions (Aguilera et al 2004, Ozen et al 2011. Unraveling the precise role of ILP molecules in H. pylori-related carcinogenesis may provide novel pharmacological targets for microorganism-related cancers.…”
Section: Insulin Resistance Infection and Cancermentioning
confidence: 99%